Influence of Soil Layers on the Infiltration Rates and Cumulative Infiltration Using Modified Green Ampt Model in the HYDROL-INF Simulation Environment - Mosammat Mustari Khanaum; Md. Saidul Borhan (Hasanuddin University, 2022)
Soil profiles are generally heterogeneous and consist of various horizontal layers due to geological processes, the formation of crusts, or other artificial or man-made activities. To quantify infiltration into these heterogeneous soil profiles, the Modified Green-Ampt Model (MGAM) is a physically-based hydrologic model that can efficiently perform under both steady and unsteady rainfall events. Based on the secondary data, this study sought to determine the effect of changing soil layers (soil textures) on infiltration rates and cumulative infiltrations in in both laboratory and field settings. Different scenarios were analyzed by rearranging soil layers and evaluating their impacts on corresponding infiltration rates and cumulative infiltrations. Simulations were run with HYDROL-INF software environment using MGAM. Three scenarios were considered for a laboratory experiment with two different types of soil texture coupled with five different soil profiles. Similarly, four scenarios were considered for the field experiments with five different types of soil texture couple with eight different soil profiles. The simulated infiltration rates and cumulative infiltrations were found to vary with soil layer change scenarios. The simulated cumulative infiltrations, ponding times, infiltrating rates at ponding, and total depth of wetting front at ponding of a five-layered laboratory soil column were identical for the three scenarios. Simulated cumulative infiltrations were 33.16, 23.65, 21.29, and 42.77 cm, respectively, for scenarios (combinations) 1, 2, 3, and 4 in the eight-layered soil profile in the field scenarios. Infiltration rates among scenarios at ponding were identical (0.46 to 0.53 cm/h) with field scenario data.